Access to End-of Life Parkinson's Disease Patients Through Patient-Centered Integrated Healthcare - Eggers, Carsten; Dano, Richard; Schill, Juliane; Fink, Gereon R.; Timmermann, Lars; Voltz, Raymond; Golla, Heidrun; Lorenzl, Stefan (Frontiers in Neurology, 2018)
Background: Palliative care in Parkinson’s Disease (PD) patients considerably differs from palliative care in oncology patients. Integrated care models are a concept to support patients and improve management of PD symptoms. However, it is not known if the access to PD patients at the end of life can be achieved through integrated care models. Aim: To analyze an integrated model of care for PD patients with the aim to identify if this integrated model of care has access to PD patients at the end of life. Material & Methods: The Cologne Parkinson’s network was designed as a randomized, controlled prospective clinical trial in order to increase quality of life of PD patients. This innovative model of care integrated a neurologist in private practice, a movement disorder specialist of the University Hospital and a PD nurse. Mortality rates of PD patients during the study period of six months were registered and compared with mortality rates of the general population of Germany according to the Federal Statistical Office of Germany. The retrospective post-hoc analysis was conducted after completion of the initial study at the University Hospital and neurologists’ practices in the greater area of Cologne, Germany. Eligible patients had a diagnosis of idiopathic PD and were aged 25-85 years. Results: PD patients in this trial had an even slightly lower mortality rate as the general population (1.66% v. 2.1%). These results are contradictory and speak for a substantial proportion of late-stage disease patients, who have not been adequately included in this study or have been better treated within this trial. The mean disease duration of patients in this study was around 6 years which resembles the lower range of the mean disease duration at death of PD patients in general. Conclusions: The results of our post-hoc analysis show, that accessing PD patients in the last phase of their disease is extremely difficult and nearly fails in spite of an integrated care approach. Reasons for poor access and loss of follow-up at the end of life have to be identified and care models for PD patients until the end of life should be